1986
DOI: 10.1159/000100138
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Affects the Central Mechanisms of Regulation of Heart Rate

Abstract: The effect of spinal cord stimulation (SCS) on heart rate (HR) was studied in 25 patients without cardiological symptoms, who were undergoing SCS for various reasons. HR at rest signifïcantly decreased during SCS. Physiological and pharmacological maneuvers of sympathetic and parasympathetic activation or blockade before and during SCS indicate that SCS interferes with the central mechanisms of regulation of HR mainly by inducing a functional sympathectomy, and that such an effect is mediated by an action on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 3 publications
0
22
0
1
Order By: Relevance
“…7,8 Although CSCS can augment blood flow in most brain regions, including the MCA core and regions bordering the core, other potential mechanisms must be considered. 8 CSCS may increase activity in the brain stem and can lead to a decrease in cervical sympathetic tone, 21 both of which are neuroprotective. 22 In a combined ischemic and traumatic model in the rabbit, spinal cord stimulation leads to a reduction in lesions and attenuation of the CBF decrease caused by the insult.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although CSCS can augment blood flow in most brain regions, including the MCA core and regions bordering the core, other potential mechanisms must be considered. 8 CSCS may increase activity in the brain stem and can lead to a decrease in cervical sympathetic tone, 21 both of which are neuroprotective. 22 In a combined ischemic and traumatic model in the rabbit, spinal cord stimulation leads to a reduction in lesions and attenuation of the CBF decrease caused by the insult.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of neurostimulation has been linked to a form of sympathectomy [11,14]. Indeed sympathectomy is used to treat angina, and Apthorp et al [15] found that it relieved angina in about 75% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in exercise tests spinal cord stimulation applied in the treatment of angina pectoris has shown to increase the patients' working capacity, to increase the period of exercise before angina and to reduce the recovery time [10]. It has also been revealed that heart rate decreased significantly during rest when spinal cord stimulation was used [11]. These beneficial results may be explained by reduced sympathetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a α 2 agonist, clonidine in high doses suppressed SCSinduced vasodilation. Also some patients demonstrated vasodilation with SCS even after chemical or surgical sympathectomy (Meglio et al, 1986;Broseta et al, 1986;Jacobs et al, 1988). It should be noted that, in humans, sympathectomy is rarely total.…”
Section: Sympathetic Mechanism-itmentioning
confidence: 99%